Amazonia in Brazilian military thought: Army and Navy conceptual frameworks and strategic actions in the 90s - Pivatto Junior, Dilceu Roberto (2020)
Defending Amazonia is one of the main priorities of the Brazilian Armed Forces. Since the 1980’s and 1990’s national policies for this region have been subject to increasing pressures, both domestic and external. These have prompted new government strategic initiatives such as the Calha Norte Project (1985) and the SIVAM (1990). Due to budgetary restrictions, a redeployment of troops and military units towards the north and northwest of Brazil was necessary, in addition to the development of new strategies and doctrines. This reorganization has not been sufficiently studied in the available academic literature.  This article attempts to address this neglect and analyses the main strategic approaches adopted by the Brazilian Army and Navy towards Amazonia during the 1990s. The research has applied a discursive institutionalist perspective, using official documents and specialized military magazines as its main sources, in addition to interviews with officers who held important positions in the period under review, including former ministers and force commanders. The article concludes that, throughout the investigated period, the thinking of the army and of the navy tended to converge into the need to increase overall military presence in the region. The end of the Cold War and the rise of new issues in the regional security agenda such as drug trafficking and the environment, led the Brazilian military to rethink its defense strategy, developing new hypotheses of regional conflict which included the potential  participation of extra-continental powers.